2017
DOI: 10.1002/2017gl073726
|View full text |Cite
|
Sign up to set email alerts
|

Seismically invisible fault zones: Laboratory insights into imaging faults in anisotropic rocks

Abstract: Phyllosilicate‐rich rocks which commonly occur within fault zones cause seismic velocity anisotropy. However, anisotropy is not always taken into account in seismic imaging and the extent of the anisotropy is often unknown. Laboratory measurements of the velocity anisotropy of fault zone rocks and gouge from the Carboneras fault zone in SE Spain indicate 10–15% velocity anisotropy in the gouge and 35–50% anisotropy in the mica‐schist protolith. Greater differences in velocity are observed between the fast and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 45 publications
(62 reference statements)
1
14
0
Order By: Relevance
“…The use of FZGWs is critically dependent on the velocity contrast between the fault and the country rock and the orientation of any anisotropic fabric in the country rock. If the slow direction of any anisotropy is oriented perpendicular to the low-velocity fault zone, seismic energy may escape the low-velocity zone, making the fault difficult to recognize through FZGWs [Kelly et al, 2017]. The seismic velocities and anisotropies reported in this study support previous regional observations on the behavior Journal of Geophysical Research: Solid Earth 10.1002/2017JB014355 of seismic waves on the Alpine Fault, where the fault core material has lower seismic velocities than the fastest direction in the country rock hosting it and the heterogeneity of microstructures within the fault zone serves to homogenize any anisotropy [Eccles et al, 2015].…”
Section: Implications For Fault Zone Properties During the Seismic Cyclementioning
confidence: 99%
“…The use of FZGWs is critically dependent on the velocity contrast between the fault and the country rock and the orientation of any anisotropic fabric in the country rock. If the slow direction of any anisotropy is oriented perpendicular to the low-velocity fault zone, seismic energy may escape the low-velocity zone, making the fault difficult to recognize through FZGWs [Kelly et al, 2017]. The seismic velocities and anisotropies reported in this study support previous regional observations on the behavior Journal of Geophysical Research: Solid Earth 10.1002/2017JB014355 of seismic waves on the Alpine Fault, where the fault core material has lower seismic velocities than the fastest direction in the country rock hosting it and the heterogeneity of microstructures within the fault zone serves to homogenize any anisotropy [Eccles et al, 2015].…”
Section: Implications For Fault Zone Properties During the Seismic Cyclementioning
confidence: 99%
“…In addition, rocks formed within fault shear zones develop strong intrinsic elastic anisotropy from the alignment of platy minerals (such as mica) and foliation (Christensen, 1965;Jones & Nur, 1982;Shea & Kronenberg, 1993). The combined effects of seismic anisotropy and mechanical damage result in nonunique solutions when attempting to constrain the fault structure and physical properties from seismic waves (Dempsey et al, 2011;Gulley et al, 2017;Kelly et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent work has documented seismic anisotropy across the damage zone of the San Andreas fault due to the development of clay and clay fabrics, providing support for the argument that the fault may be mechanically weak and exhibit creep due to intrinsically weak fault materials (Jeppson & Tobin, 2015). A similar study focused on the Carboneras fault zone in southeast Spain found that the degree of seismic anisotropy in the fault zone varies as a function of fabric and foliation, indicating that these characteristics are important to consider when designing source‐receiver geometries for seismic surveys and imaging of fault zones (Kelly et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This peak and subsequent decay has been attributed to the formation and evolution of shear planes and fabrics (Haines et al, 2013;Ikari et al, 2009;Knuth et al, 2013;Logan & Rauenzahn, 1987;Saffer & Marone, 2003). While many of the effects of shear fabrics and clays, and smectite clay in particular, are well studied (e.g., decrease in coefficient of friction and evolution of porosity), there are comparatively few studies of the combined effects of composition, shear fabric, and fault structure on the elastic properties of fault zones (Carpenter et al, 2014;Gettemy et al, 2004;Jeppson & Tobin, 2015;Kelly et al, 2017;Knuth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation